PREVENTION OF ADHESIONS AFTER SURGICAL INTERVENTIONS IN GYNECOLOGY (Academicia Globe: Inderscience Research, 2021)
A comprehensive examination was carried out in 108 patients after surgical interventions on the appendages and fallopian tubes with a different volume of rehabilitation measures. It is revealed that the inclusion complex of events preventing postoperative adhesions process drugs having immunomodulatory effect together with prolonged hyaluronidase activity, it allows to compensate the negative impact operation injury on the immune system. Clinical evidence of the effectiveness of therapy ELISA waking - elk reduction in both the frequency and severity of adhesions, which reduced the number of reconstructive surgery for infertility in these patients.